Exploring neurodevelopmental concerns: insights from a public neuropediatric learning disabilities multiprofessional outpatient facility in Brazil - Augusto, Janaína Aparecida de Oliveira; Ferreira, Thalita Francielli Lopes; Arduini, Rodrigo Genaro; Bastos, Talita Meneses de Almeida; Campanha, Nádia Santana Pereira; Fornasari, Rita de Cássia Coutinho Vieira; Stella, Patrícia Regina Flaviano; Simão, Adriana Nobre de Paula; Moraes, Joyce Nelly Leal de; Ciasca, Sylvia Maria (Frontiers in Psychology, 2025)
IntroductionSpecialized public services for attending children and adolescents with complaints of scholar difficulties are scarce in Brazil. It is important to recognize this target population and understand its demands, so these facilities may be able to meet their needs and offer qualified and effective services. The main objective of this study was to characterize the profile of neuropediatric patients cared for in a reference outpatient facility in Brazil.MethodData were extracted from children’s and adolescent’s records, corresponding to assessments carried out between March 2017 to March 2023.ResultsFrom 220 selected records, 70% had complaints related to learning difficulties and 79.1% to attention disorders. The most frequent diagnoses were attention-deficit/hyperactivity disorder (30%), intellectual deficiency (19.1%), and learning-specific disorder (17.7%). A significant association with scholarship was found between motor agitation [χ2(9) = 29.8; p < 0.001], behavioral complaints [χ2(9) = 16.2; p = 0.050], and language difficulties [χ2(9) = 17.0; p = 0.043]. Results have indicated significant differences relating to diagnosis and gender: boys had a higher prevalence for dyslexia [χ2(1) = 4.44; p = 0.035], intellectual deficiency [χ2(1) = 8.38; p = 0.004], and autism spectrum disorder [χ2(1) = 9.29; p = 0.002], when compared to girls.ConclusionThese results corroborate international findings over complaints regarding learning difficulties and correlated disturbances, in addition to the existing comorbidities between different diagnoses related to neurodevelopment and scholar acquisitions.